Influence of native lactic acid bacteria on the microbiological, biochemical and sensory profiles of Serra da Estrela cheese - Macedo, Angela C. (2011)
Cheesemaking from batches of raw ewe’s milk was carried out via inoculation with wild strains of Lactococcus lactis subsp. lactis ESB110019 and Lactobacillus plantarum ESB5004 independently, or combined with each other. Those two strains had been isolated from the native microflora of typical Serra da Estrela cheese. One control batch was processed in parallel without addition of any starter. The evolution in viable counts of the main micro-organisms (viz. lactic acid bacteria, Enterobacteriaceae, staphylococci and yeasts), as well as in secondary proteolysis (WSN, 2% TCASN, 12% TCASN and 5% PTASN), was monitored throughout ripening time (over a 63-day period) in cheeses from each batch. The sensory features of the fully ripened cheeses were also assessed. Cheeses manufactured with starter showed significantly lower levels of viable Enterobacteriaceae than those manufactured without starter; viable counts of enterococci and staphylococci did significantly increase after addition of L. lactis or Lb. plantarum, respectively. Proteolysis in terms of WSN and 5% PTASN was not significantly affected by the lactic acid bacteria tested when compared to the control, but L. lactis played a significant role toward increasing the 2% TCASN content of cheeses; both strains led to a statistically significant increase of the 12% TCASN. The scores for flavor and texture of the control cheeses were somewhat above those for the experimental cheeses manufactured with starter.